MODEL-MODEL PEMBELAJARAN BAHASA INDONESIA - Yuken Novi Yanti Br Sirait; Silvina Noviyanti; Ahmad Syarif; Juita Dalimunthe; Aurora Karina Tomia Putri; Vivi Ade Novri Yanty Napitu (STKIP Subang, 2026)
Indonesian language learning plays a strategic role in developing students’ language competencies, including listening, speaking, reading, and writing skills. However, instructional practices in the classroom are still predominantly characterized by conventional approaches that tend to inadequately promote student engagement and active participation. Therefore, the implementation of innovative learning models that are relevant to students’ characteristics is necessary. This study aims to describe various models of Indonesian language learning and to analyze the advantages of each model in improving the quality of the learning process and outcomes. The method employed in this study is a literature review using a descriptive qualitative approach through the analysis of various scientific sources, including journals, books, and relevant articles published within the last five years. The findings indicate that Problem Based Learning, Project Based Learning, Discovery Learning, Inquiry Learning, and Contextual Teaching and Learning models have significant contributions in enhancing student engagement, critical thinking skills, and learning outcomes. Thus, the selection and implementation of appropriate learning models are essential in achieving effective, innovative, and meaningful Indonesian language learning.